PEGARUH MODEL PEMBELAJARAN CREATIVE PROBLEM SOLVING TERHADAP KETERAMPILAN BERPIKIR KREATIF PADA SISWA KELAS V SD - Yusfirda Rahmah Rezkiana; Galuh Kartika Dewi; Lita Erdiana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2023)
This study intends to determine the impact of Creative Problem Solving (CPS) on student’s creative thinking as well as the reactions of students to the use of Creative Problem Solving technique. This lack of student participation in the teaching and learning processes is what motivated the researcher to conduct this study. The only teaching strategy that can improve student’s ability for creative though is Creative Problem Solving. One group pre-test and post-test models were employed in the quantitative model for this study. This study was carried out for fifth grades students at SDN Lemahputro 1 Sidoarjo. With fiftheen 15 students served as the sample for this research. The results of the student questionnaires and a paired sample T-test with a sig. 0,05 were employed in this study. The outcame of the hypothesis measurement is 0,00 because 0,00 < 0,05, meaning that H1 was rejected since it could be inferred that the creative problem solving approach had an impact on student’s creative thinking. As 85% of the students responded to the questionnaires, it is reasonable to assume that they were quite comfortable with the creative problem solving method.